Alternative dispute resolution procedures using information technologies: legal regulation in the European Union and the USA - Аракелян, Мінас Рамзесович; Аракелян, М. Р.; Аракелян, Минас Рамзесович; Arakelian, Minas R.; Arakelian , Minas; Іванченко, Ольга Миколаївна; Іванченко, О. М.; Иванченко, Ольга Николаевна; Ivanchenko, Olha M.; Ivanchenko, Olga; Тодощак, Олег Володимирович; Тодощак, О. В.; et al. (Universidad de la Amazonia, 2020)
The article is devoted to the research of legal issues of protection of the violated rights, determination of the effectiveness of the mechanism of ensuring the rights, investigation of alternative ways of protection of rights, analysis of the functioning of ODR platforms and prospects of their functioning. The article notes that with the widespread use of the Internet, legal institutions are changing, especially with regard to dispute resolution. The emergence of e-commerce has led to the emergence of online dispute resolution platforms that are already in use on all continents. The e-commerce market in Ukraine and in the world is gaining momentum, so Ukraine's desire for closer interaction with EU Member States and integration into the common market necessitates a detailed study of the experience of the EU and foreign countries to introduce the most effective and advanced mechanisms for securing the rights of e-commerce participants. The study concludes that it is advisable to use online dispute resolution (ODR) procedures, which are a cross-border alternative dispute resolution, as a fast and versatile way to resolve disputes, as a substitute for the ineffective existing forms of IPR protection. Based on the analysis of the existence of alternative dispute resolution methods, it is established that online dispute resolution due to its specific legal nature is an independent way of resolving disputes.

Стаття присвячена дослідженню правових питань захисту порушених прав, визначенню ефективності механізму забезпечення прав, дослідженню альтернативних способів захисту прав, аналізу функціонування ODR-платформ та перспектив їх функціонування . У статті зазначається, що із широким використанням Інтернету юридичні інститути змінюються, особливо щодо вирішення спорів. Поява електронної комерції призвела до появи онлайн-платформ вирішення суперечок, які вже використовуються на всіх континентах. Ринок електронної комерції в Україні та у світі набирає обертів, тому прагнення України до більш тісної взаємодії з державами-членами ЄС та інтеграції до спільного ринку вимагає детального вивчення досвіду ЄС та зарубіжних країн для впровадження найбільш ефективних вдосконалених механізмів забезпечення прав учасників електронної комерції. В дослідженні зроблено висновок, що доцільно використовувати процедури онлайн-врегулювання суперечок (ODR), які є транскордонним альтернативним вирішенням спорів, як швидкий та універсальний спосіб вирішення суперечок, як замінник неефективних існуючих форм захисту прав інтелектуальної власності. На основі аналізу існуючих альтернативних методів вирішення спорів встановлено, що онлайн-вирішення спорів через свою специфічну правову природу є самостійним способом вирішення спорів.

Статья посвящена исследованию правовых вопросов защиты нарушенных прав, определению эффективности механизма обеспечения прав, исследованию альтернативных способов защиты прав, анализу функционирования ODR-платформ и перспектив их функционирования. В статье отмечается, что с широким использованием Интернета юридические институты меняются, особенно в контексте разрешения споров. Появление электронной коммерции привело к появлению онлайн-платформ разрешения споров, которые уже используются на всех континентах. Рынок электронной коммерции в Украине и в мире набирает обороты, поэтому стремление Украины к более тесному сотрудничеству с государствами-членами ЕС и интеграции в общий рынок требует детального изучения опыта ЕС и зарубежных стран для внедрения наиболее эффективных усовершенствованных механизмов обеспечения прав участников электронной коммерции. В исследовании сделан вывод, что целесообразно использовать процедуры онлайн-урегулирования споров (ODR), которые являются трансграничным альтернативным решением споров, как быстрый и универсальный способ разрешения споров, как заменитель неэффективных существующих форм защиты прав интеллектуальной собственности. На основе анализа существующих альтернативных методов разрешения споров установлено, что онлайн-решение споров благодаря своей специфической правовой природе является самостоятельным способом решения споров.
Arakelian M. Alternative dispute resolution procedures using information technologies: legal regulation in the European Union and the USA / M. Arakelian, O. Ivanchenko, O. Todoshchak // Amazonia Investiga. - V. 9 (26). - Universidad de la Amazonia, 2020. – P. 60-67.
Keywords: оnline dispute resolution; alternative dispute resolution procedures; international practice; protection of rights; extrajudicial order; mediation; онлайн-вирішення суперечок; процедури альтернативного вирішення спорів; міжнародна практика; захист прав; позасудовий порядок; медіація; онлайн-разрешение споров; альтернативные процедуры разрешения споров; международная практика; защита прав; внесудебный порядок; медиация; Research Subject Categories::LAW/JURISPRUDENCE